A.T. STILL (1828–1917), THE FOUNDER OF OSTEOPATHY: THE COURSE OF LIFE - V. I. Karpova; V. V. Tarasova; N. A. Tarasov (Русский журнал детской неврологии, 2016)
Osteopathy is a young medical specialty that has found official acceptance in Russia since 2013. The paper deals with the history of osteo pathy and its founder Andrew Taylor Still (1828–1917). He left a few printed scientific works, including his biography reporting much of his life and activities and the creation of osteopathy. The emergence date of osteopathy is considered to be 22 June 1874. Historically, modern osteopathy has come into existence not so long. We are almost contemporaries of it and its author, but despite this, the international osteopathy community is romanticizing and mythologizing the personality of A.T. Still. In our opinion, the reason is his magnetic personality and brilliant life. Thanks to A.T. Still’s personality, osteopathy may not have been lost among many medical areas and discoveries and continues to develop and attract new supporters. On the other hand, osteopathy is, in the opinion of its founder, a science; therefore a historical rather than mythological approach to A.T. Still’s bibliography, which takes into account all factors for personality formation, is considered correct. Modern science tells that these factors are inheritance, environment, and education. The authors have applied just this scientific approach and, without demolishing the myths, set forth an aim to study the factors forming the world outlook of A.T. Still in order to predict a further way to develope osteopathy in our country.